2022
DOI: 10.21037/gs-21-642
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of extended surgical resections for locally advanced thymic malignancies: a narrative review

Abstract: Background and Objective: Thymic malignancies represent the most common anterior mediastinal neoplasms, as well as rare and challenging tumors. Surgery is the cornerstone in the treatment of thymic malignancies, although a multidisciplinary approach is mandatory, for both, locally advanced or metastatic disease. In our narrative review, we explored the recent literature to investigate clinical and radiological assessment, multimodality approach and outcomes of locally advanced thymic tumors. More than one-thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Also according to the literature, the role for MIS in the case of extended surgery for thymic neoplasms is still controversial and remains mainly correlated with anatomical features, abilities of surgeon and multidisciplinary attitude [9]. Soder and co-workers [22] retrospectively analyzed a monocentric 20-year experience in thymic surgery comparing open and robotic approach: They find a significant reduction in PC in the robotic group (6.8% versus 21.1%) despite a significant greater proportion of extended resections in the robotic group after a propensity score match.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Also according to the literature, the role for MIS in the case of extended surgery for thymic neoplasms is still controversial and remains mainly correlated with anatomical features, abilities of surgeon and multidisciplinary attitude [9]. Soder and co-workers [22] retrospectively analyzed a monocentric 20-year experience in thymic surgery comparing open and robotic approach: They find a significant reduction in PC in the robotic group (6.8% versus 21.1%) despite a significant greater proportion of extended resections in the robotic group after a propensity score match.…”
Section: Commentmentioning
confidence: 99%
“…Conversely, in a small retrospective study, Chen [23] compared VATS and open surgery in the treatment of Masaoka stage III thymomas and they found that phrenic nerve and vena cava resection was more likely to be performed by open surgery rather than VATS. Nonetheless, in the vast majority of reported experiences, complex extended resections are performed by open sternotomy, thoracotomy or clamshell incision [3, 9, 21, 24, 25].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the use of robot-assisted surgical techniques is continuously increasing, given the better surgical field offered and the possibility to articulate the instruments, allowing a precise and adequate dissection. Partial or total sternotomy is, of course, still used, but is reserved for huge masses and advanced cases with invasion of surrounding organs or structures, in particular great vessels [ 104 , 105 ].…”
Section: Diagnostic and Therapeutic Approachesmentioning
confidence: 99%
“…Thymic epithelial tumors (TETs) are one of the most common primary tumors in the mediastinum, accounting for up to 50% of all anterior mediastinal neoplasms in adults [ 1 , 2 ]. Incidental thymus tumors are almost always asymptomatic and appropriate serum markers are absent, so the clinician’s decision-making on treatment largely depends on imaging findings.…”
Section: Introductionmentioning
confidence: 99%